Development of a novel adenovirus type 4 vector as a promising respiratory vaccine vehicle - Xu, Jinghan; Wang, Busen; Zhao, Zhenghao; Wu, Shipo; Zhang, Zhe; Liu, Shuling; Huo, Nan; Zheng, Wanru; Chen, Yi; Gao, Zhiqiang; Jia, Zuyuan; Liu, Tianyu; et al. (Frontiers in Immunology, 2025)
IntroductionAdenovirus (Ad) vectors are widely used for gene delivery, and some of them have been approved for vaccine development. In particular, the recombinant COVID-19 vaccine for inhalation, which was developed using adenovirus type 5 (Ad5), represents a milestone in respiratory immunization. Owing to the high pre-existing immunity (PEI) to Ad5, the development of an adenoviral vector with lower PEI and higher immunogenicity has been explored. However, the majority of the developed novel Ad vectors showed suboptimal immunogenicity compared to Ad5 in animal models.MethodIn this study, we constructed a novel replication-deficient viral vector based on human adenovirus type 4 (Ad4), which has long been used as a live virus vaccine with a favorable safety profile in the U.S. military. The mice were immunized intramuscularly or intranasally with an Ad4-vectored vaccine to verify immune responses and protective efficacy.ResultsCompared with Ad5, the novel Ad4 vector showed comparable viral growth kinetics and transgene expression in cells and similar exogenous protein expression and distribution in mice. Furthermore, the Ad4-vectored vaccine elicited superior humoral and cellular responses and protective effects when vaccinated intranasally than those triggered by the Ad5-vectored vaccine. Finally, the heterologous Ad5 prime and Ad4 boost immunization showed better immunogenicity and protective efficacy.DiscussionThis study broadens the research trajectory of adenovirus-vectored vaccines and offers a new option for the development of recombinant viral-vectored vaccines.